Peculiarities of the course of dental caries in pregnant women of different age - I. K. Lukashevich; I. L. Gorbunova (Acta Biomedica Scientifica)
Clinical course of dental caries during pregnancy has some peculiarities. However, significant differences in indicators to characterize oral hygiene and teeth soft plaque cariogenicity between the studied groups have not been revealed. In analyzing the prevalence of caries resistance levels allocation among pregnant women aged up to 30 years the representatives of high, average, and low resistance levels have been noticed. In the group of pregnant women aged above 30 years the patients with average, low, and very low levels of caries resistance have been presented. During the observation period, some caries resistance worsening has been determined in both age groups. Herein there was changing the average level into the low one, as well as the low level into the very low one at the age group above 30 years. In the age group up to 30 years the transition of the high level caries resistance to the average one, but the average level into the low level has been occurred. In this connection, there is the assumption that tissue resistance of teeth enamels likely to be primarily determined by its physicochemical parameters caused by genetics. The role of oral fluid as the medium surrounding teeth is likely to have importance. Advanced studying the oral cavity organs and tissues state in pregnant women allowed to implement a strategy of individualized approach to the early dental caries diagnostics in such category of patients, and to determine their stomatological curing peculiarities.